2009
DOI: 10.1523/jneurosci.0859-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

NAD+Activates KNaChannels in Dorsal Root Ganglion Neurons

Abstract: Although sodium-activated potassium channels (K Na ) have been suggested to shape various firing patterns in neurons, including action potential repolarization, their requirement for high concentrations of Na ϩ to gate conflicts with this view. We characterized K Na channels in adult rat dorsal root ganglion (DRG) neurons. Using immunohistochemistry, we found ubiquitous expression of the Slack K Na channel subunit in small-, medium-, and large-diameter DRG neurons. Basal K Na channel activity could be recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
108
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(111 citation statements)
references
References 38 publications
3
108
0
Order By: Relevance
“…Like their adult counterparts (Tamsett et al, 2009), embryonic cultured DRG neurons abundantly express the Slack subunit (Fig. 1 A).…”
Section: Cultured Drg Neurons Contain Slack K Na Channelsmentioning
confidence: 97%
See 1 more Smart Citation
“…Like their adult counterparts (Tamsett et al, 2009), embryonic cultured DRG neurons abundantly express the Slack subunit (Fig. 1 A).…”
Section: Cultured Drg Neurons Contain Slack K Na Channelsmentioning
confidence: 97%
“…K Na channels are abundantly expressed in the cell bodies and axons of nociceptive DRG neurons (Bischoff et al, 1998;Tamsett et al, 2009), and suggested to regulate DRG neuronal resting membrane potential (RMP) (Bischoff et al, 1998). In neuronal simulations, K Na channels caused firing accommodation Brown et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Mutational analyses indicated that Na ϩ binding and gating occur in RCK domain 2 (Zhang et al, 2010). Slack channels are widely expressed throughout the rat central nervous system, including the substantia nigra (SN), but also are abundantly expressed in peripheral dorsal root ganglion (DRG) neurons (Bhattacharjee et al, 2002;Tamsett et al, 2009). Because Slack channels are activated by both voltage and cytosolic factors such as intracellular Na ϩ and Cl Ϫ , they are ideal effectors of negative feedback during neuronal excitation.…”
Section: Introductionmentioning
confidence: 99%
“…The channels expression pattern and its potential to contribute to elevated firing rates are consistent with a role in the pathogenesis of epilepsy. In the last decade research has also shown that these channels have additional modulatory functions, which are regulated by a number of signaling pathways [5][6] . The majority of the recently identified mutations [7][8][9][10] are situated in the c-terminus of the alpha subunit of KCNT1, where modulatory regions, such as the NAD + binding domain [5] and several putative consensus sites for protein kinase C (PKC) [6] are located.…”
Section: Research Highlightmentioning
confidence: 99%
“…In the last decade research has also shown that these channels have additional modulatory functions, which are regulated by a number of signaling pathways [5][6] . The majority of the recently identified mutations [7][8][9][10] are situated in the c-terminus of the alpha subunit of KCNT1, where modulatory regions, such as the NAD + binding domain [5] and several putative consensus sites for protein kinase C (PKC) [6] are located. Emerging evidence indicates that subtle changes in the function of this channel have a deleterious impact on the fragile developing brain [7][8][9][10] .…”
Section: Research Highlightmentioning
confidence: 99%